Molecular analysis of the bacterial communities in the live Pacific oyster (Crassostrea gigas) and the influence of postharvest temperature on its structure - Fernandez Piquer, J; John Bowman; Thomas Ross; Mark Tamplin (2012)
Aims: To evaluate the effect of postharvest temperature on bacterial communities in live Pacific oysters ( Crassostrea gigas ) using nonculture-based methods. Methods and Results: Live oysters were compared before and after storage at 4, 6, 15, 20 and 30 Celsius Degree using terminal restriction fragment length polymorphism (T-RFLP). Bacterial communities in freshly harvested (control) vs stored oysters were significantly different. Changes in bacterial communities at 4, 15 and 30 Celsius Degree observed by T-RFLP were further investigated by clone library analysis. Members of the Proteobacteria predominated (43.0-57.0% of clones) in control oysters, while storage altered the bacterial profile. At 4 Celsius Degree, Psychrilyobacter spp.(phylum Fusobacteria ) predominated (43.8% of clones), while at 15 and 30 Celsius Degree, members of the phylum Bacteroidetes represented 63.0 and 60.2% of clones, respectively. High microbial diversity in oysters was observed, with at least 73 different genera-related clones among all samples. Conclusions: Changes in the overall bacterial community of Pacific oysters were influenced by storage temperature and would likely not be detected by standard culture-based methods currently used to assess oyster quality. Certain dominant genera, such as Psychrilyobacter , Polynucleobacter and a bacterial group related to Alkaliflexus , should be further studied as possible indicators for postharvest temperature control. Significance and Impact of the Study: This work is the first report describing the effect of different storage temperatures on bacterial diversity in postharvest live Pacific oysters using molecular-based methods.